A New Model of Solar Ultraviolet Irradiance Variability With 0.1–0.5 nm Spectral Resolution. Issue 10 (13th October 2022) - Lean, J. L.; Coddington, O.; Marchenko, S. V.; DeLand, M. T.
Abstract: Observations of solar irradiance made from space since 2003 with 0.1 nm spectral resolution at wavelengths from 115 to 310 nm and 0.5 nm spectral resolution at wavelengths from 260 to 500 nm are used to construct a new model, NRLSSI2h, of solar irradiance variability with higher spectral resolution than the 1 nm NRLSSI2 model used to specify the NOAA Solar Irradiance Climate Data Record. The new model better resolves irradiance variability in specific emission and absorption features that are directly attributable to atoms and molecules in the Sun's atmosphere. Singularly prominent is spectral irradiance variability at 379–389 nm, dominated by the CN molecular band system; irradiance in this 10 nm band increased 0.078 W m −2 during solar cycle 23, contributing 4.6% of the 1.7 W m −2 concurrent total solar irradiance increase. Irradiance variability at wavelengths from 300 to 400 nm, a region dominated by multiple spectral features, is a factor of 2–5 smaller in the new model than estimated by semiempirical models that use radiative transfer codes to calculate the contrasts of faculae and sunspots, which alter the temperature‐dependent densities of these species relative to the surrounding continuum. Solar atmosphere temperature and composition profiles in radiative transfer models may therefore not be realistic or their atomic and molecular databases may be incomplete. Improved colocation of spectral features in solar irradiance and the absorption cross sections of molecular oxygen and ozone with the new model may allow higher fidelity calculations of energy deposition in Earth's atmosphere. Key Points: A new high‐resolution (0.1–0.5 nm) solar irradiance variability model, NRLSSI2h, captures larger UV spectral line variability At 300–400 nm, where spectral features dominate, NRLSSI2h estimates 2–5 times less solar cycle variability than radiative transfer models Atmospheric absorption of solar radiation differs using NRLSSI2h relative to the 1 nm NRLSSI2 model (at 121.6 nm, 34% decrease at 88 km)